2020
DOI: 10.17221/115/2019-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Chemical analyses and evaluation of the anthelmintic effects of Origanum majorana essential oil, in vitro and in vivo studies

Abstract: Because of the development of resistance in helminths against major anthelmintic drugs, the search for alternatives is necessary. Medicinal plants are being studied as an alternative source of anthelmintics against gastrointestinal nematodes. The objective of this study is to analyse the chemical composition and evaluate the anthelmintic efficacy of Origanum majorana essential oil. The determination of the chemical composition by gas chromatography/mass chromatography (GC/MS) revealed that the essential oil wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Chemotype-4 is dominated by linalool [59,60] and is comprised of three samples. The chemotype-5 is dominated by carvacrol, which is comprised of four samples [38,[61][62][63].…”
Section: Chemotypes Of O Majorana Eosmentioning
confidence: 99%
“…Chemotype-4 is dominated by linalool [59,60] and is comprised of three samples. The chemotype-5 is dominated by carvacrol, which is comprised of four samples [38,[61][62][63].…”
Section: Chemotypes Of O Majorana Eosmentioning
confidence: 99%
“…[15][16][17][18] A recent study demonstrated significant anthelmintic activity of the leaves and stems of Origanum majorana and attributed it to the presence of p-cymene, carvacroland thymol . 19 The reference of Piper longum comes from ancient times for its medicinal and dietary uses. 20 In the present study methanolic extract of Piper longum showed better anthelmintic activity as compared to the aqueous extract.…”
Section: Discussionmentioning
confidence: 99%
“…Some EO compounds such as menthol are of very low acute oral toxicity (LD50 > 2000 mg/Kg) (Chagas et al 2018). Oral administration of the EO of Origanum majorana at different doses of 1000-5000 mg/Kg displayed no signs of toxicity, nor caused fatal effects in any of the treated mice during an observation period of 24 hours (Abidi et al 2020). Katiki et al (2012) concluded that Cymbopogon schoenanthus is safe for sheep at the doses of 180 mg/Kg and 360 mg/Kg, since no significant differences among group means for the hepatic (enzymes) or kidney (urea and creatinine) parameters were recorded after treatment with EO.…”
Section: Toxicity Studiesmentioning
confidence: 99%